Case study of a humidity layer above Arctic stratocumulus and potential turbulent coupling with the cloud top - Egerer, Ulrike; Ehrlich, André; Gottschalk, Matthias; Griesche, Hannes; Neggers, Roel A.J.; Siebert, Holger; Wendisch, Manfred (Katlenburg-Lindau : European Geosciences Union, 2021)
Specific humidity inversions (SHIs) above low-level cloud layers have been frequently observed in the Arctic. The formation of these SHIs is usually associated with large-scale advection of humid air masses. However, the potential coupling of SHIs with cloud layers by turbulent processes is not fully understood. In this study, we analyze a 3 d period of a persistent layer of increased specific humidity above a stratocumulus cloud observed during an Arctic field campaign in June 2017. The tethered balloon system BELUGA (Balloon-bornE moduLar Utility for profilinG the lower Atmosphere) recorded vertical profile data of meteorological, turbulence, and radiation parameters in the atmospheric boundary layer. An in-depth discussion of the problems associated with humidity measurements in cloudy environments leads to the conclusion that the observed SHIs do not result from measurement artifacts. We analyze two different scenarios for the SHI in relation to the cloud top capped by a temperature inversion: (i) the SHI coincides with the cloud top, and (ii) the SHI is vertically separated from the lowered cloud top. In the first case, the SHI and the cloud layer are coupled by turbulence that extends over the cloud top and connects the two layers by turbulent mixing. Several profiles reveal downward virtual sensible and latent heat fluxes at the cloud top, indicating entrainment of humid air supplied by the SHI into the cloud layer. For the second case, a downward moisture transport at the base of the SHI and an upward moisture flux at the cloud top is observed. Therefore, the area between the cloud top and SHI is supplied with moisture from both sides. Finally, large-eddy simulations (LESs) complement the observations by modeling a case of the first scenario. The simulations reproduce the observed downward turbulent fluxes of heat and moisture at the cloud top. The LES realizations suggest that in the presence of a SHI, the cloud layer remains thicker and the temperature inversion height is elevated. Leibniz_Fonds ...